2007
DOI: 10.1176/appi.ajp.2007.06111861
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Decrease of the Anterior Cingulate Cortex in Anorexia Nervosa

Abstract: In anorexia nervosa, part of the global gray matter loss persists over the long run. Region-specific gray matter loss in the anterior cingulate cortex is directly related to the severity of anorexia nervosa, indicating an important role of this area in the pathophysiology of the disorder. Further research is warranted to determine the cause, specificity, and functional consequences of this structural brain change in anorexia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
4
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(162 citation statements)
references
References 32 publications
7
146
4
5
Order By: Relevance
“…7,8 Moreover, although some of these alter ations may normalize in recovered patients, 4 other studies have shown the persistence of volume alterations in recovered patients. 7,9,10 The distributed nature of these changes implies disturbances of inter regional brain connectivity, as has been observed in most other psychiatric disorders. 11,12 At the same time, the major reorganization in white matter that the brain undergoes during adolescence and early adulthood is thought to be relevant to the development of some psychi atric disorders, including anorexia nervosa.…”
Section: Introductionmentioning
confidence: 90%
“…7,8 Moreover, although some of these alter ations may normalize in recovered patients, 4 other studies have shown the persistence of volume alterations in recovered patients. 7,9,10 The distributed nature of these changes implies disturbances of inter regional brain connectivity, as has been observed in most other psychiatric disorders. 11,12 At the same time, the major reorganization in white matter that the brain undergoes during adolescence and early adulthood is thought to be relevant to the development of some psychi atric disorders, including anorexia nervosa.…”
Section: Introductionmentioning
confidence: 90%
“…MRI has been used in human studies of the cognitive component of eating disorders such as anorexia nervosa (volumetric MRI, Muhlau et al 2007; fMRI, Vocks et al 2010) or nutritional disorders such as obesity (fMRI, Killgore & Yurgelun-Todd 2010).…”
Section: Feeding Behaviormentioning
confidence: 99%
“…Parietal and occipital cortical areas also appear to repeatedly distinguish AN from controls in states of hunger and satiety during cognitive processing of food pictures [21] . Some morphologic studies revealed differences for the AN patients in terms of grey matter decrease in the anterior cingulate cortex [22] .…”
Section: Influence Of Satiety and Subjective Valence Rating On Cerebrmentioning
confidence: 99%